AN ANALYSIS OF CONTRIBUTING FACTORS IN NURSES’ ACCURACY WHILE CONDUCTING TRIAGE IN EMERGENCY ROOM - Ria Ramadhani Dwi Atmaja; Mohammad Hidayat; Mukhamad Fathoni (Journal of Nursing Science Update (JNSU), 2020)
Triage is aimed to arrange treatment priority to patients with different levels of urgency.These nurses who are responsible for triage must conduct standardized procedure. Hence,these nurse must acquire certain competency required to conduct triage. The competencyincludes basic knowledge, skills and attitude. Besides that, there are several contributingfactors playing significant role in triage procedure implementation, which is intrinsicfactors. Regarding to those factors, this study aimed to analyze those contributing factorsaffecting nurses’ accuracy in doing triage procedure in emergency room. This studyemployed correlational analytic design accompanied with cross sectional approach. Thepopulation in this study was all nurses who worked actively in the Emergency Room atRSUD in Malang Regency and Blitar City and thirty two respondents are taken as thesamples using population total method. The data is collected using observation sheetand questionnaire. The data analyzed through Partial Least Squares (PLS). It is showedthat knowledge level (p-value 0.000), skill level (p-value 0.000), attitude (p-value 0.000),intrinsic factors (p-value 0.000) are related to nurses’ accuracy in implementing triageprocedure. Therefore, based on those findings, the hospital’s management is suggested toimprove their nurses’ competency in implementing triage, especially by recommendingthem to participate in advanced emergency training and triage course.